Investigation on the properties of mortar containing palm oil fuel ash and seashell powder as partial cement replacement - Hasan, K.; Fadzil, Mat Yahaya; Karim, A.; Rokiah, Othman (Penerbit UMP, 2021)
The concept of utilizing various types of wastes, such as agricultural dumps and marine by-products, as a partial replacement of cement has gained a great interest to develop eco-friendly and economical mortars for sustainable construction. This study aims to evaluate the feasibility of using palm oil fuel ash (POFA), an agro-industrial waste by-product from palm oil mills and seashell powder (SSP) derived from seashells, a marine waste material partial replacement of cement in mortars. The water to binder (w/b) ratio of 0.49 and the sand to binder (s/b) ratio of 2.54 with 0% to 30% of ordinary portland cement (OPC) by weight was replaced with POFA and SSP, and the resulting mortar samples were tested for mechanical properties and durability in this study. The compressive strength, flexural strength, water absorption, and flow table tests were performed in this study for different percentages of POFA and SSP after 7, 28, and 130 days. The results showed that the 30% POFA incorporated mortars achieved the highest compressive strength (35.12N/mm2), flexural strength (4.06N/mm2), high density with less water absorption (4.79%) after 130 days of curing and the high strength mortar with less water flow (22.2cm) during casting. Also, it found that the 25% POFA and 5% SSP incorporated mortars attained acceptable results as supplementary cementing material. This study suggests that the POFA and SSP incorporated mortars could be used in concrete for sustainable development of construction through the efficient valorization of waste materials.